Appetite self‐regulation: Environmental and policy influences on eating behaviors. (March 2017) - Schwartz, Marlene B.; Just, David R.; Chriqui, Jamie F.; Ammerman, Alice S.
Abstract : Objective: Appetite regulation is influenced by the environment, and the environment is shaped by food‐related policies. This review summarizes the environment and policy research portion of an NIH Workshop (Bethesda, MD, 2015) titled "Self‐Regulation of Appetite—It's Complicated." Methods: In this paper, we begin by making the case for why policy is an important tool in efforts to improve nutrition, and we introduce an ecological framework that illustrates the multiple layers that influence what people eat. We describe the state of the science on how policies influence behavior in several key areas: the federal food programs, schools, child care, food and beverage pricing, marketing to youth, behavioral economics, and changing defaults. Next, we propose novel approaches for multidisciplinary prevention and intervention strategies to promote breastfeeding, and examine interactions between psychology and the environment. Results: Policy and environmental change are the most distal influences on individual‐level appetite regulation, yet these strategies can reach many people at once by changing the environment in which food choices are made. We note the need for more research to understand compensatory behavior, reactance, and how to effectively change social norms. Conclusions: To move forward, we need a more sophisticated understanding of how individual psychological and biological factors interact with the environment and policy influences.